STRATEGI PENGUATAN PENDIDIKAN KARAKTER DI SMK NEGERI 7 SEMARANG MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING - Ahmad Rizqul Baqi; Sri Suneki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The challenges of education at the high school level in the 21st century, especially in Indonesia, do not only focus on conventional issues of equity and fulfilment of access, infrastructure and education financing, but also the quality of graduates who must have intellectual expertise in their fields as well as high morality. Seeing these conditions, the availability of human resources with character is a very important need. This is done to prepare for global challenges and the nation's competitiveness, High Schools must be able to prepare generations that have competence and good character, thus the strategy of strengthening character education in learning by using the Project Based Learning learning model requires an integrated plan. The concept of character education programmatically with a good strategy such as the strategy of moral knowing, moral modelling, moral feeling ang loving, moral acting, punishment, habituation. Should be applied in every high school until students have an inseparable unity of good character (knowing, feeling, and acting) in their daily lives.